Strategic management : |b formulation, implementation, and control - Pearce II, John A. (McGraw-Hill/Irwin, 2007)
Contemporary research in strategic management, with an emphasis on conceptual tools and skills created by scholars and practitioners in the field are evident throughout STRATEGIC MANAGEMENT, 10e. Pearce and Robinson have retained high level of academic credibility and market-leading emphasis on strategic practice with this edition. This text continues to have strong support from longtime adopters and growing support in schools with a desire to provide straightforward treatment of strategic management with a practical, systematic approach. The 10th edition will once again include numerous Business Week short cases and a wide assortment of traditional, longer strategic management cases. Pearce and Robinson continue to use a unique pedagogical model they created to provide logic and structure to its treatment of strategic management which in turn makes the material more easily organized by the instructor and learned by the student.